Natrium Kromolin, Obat Penghambat Degranulasi Sel Mast, Lebih Efektif terhadap Sel Mast Jaringan Ikat Dibanding Sel Mast Mukosa - Agung Endro Nugroho (Fakultas Farmasi Universitas Setia Budi, 2009)
Cromolyn sodium is an antiallergy drug that acts by inhibiting mast cells degranulation responsible for the release of histamine, a mediator for this disease. Moreover, cromolyn sodium is used as a first line drug in asthmatic therapy. However, cromolyn sodium did not always show the inhibition effects on histamine release from mast cells in all allergy experiment models. The aim of present study was to reconfirm the effect of cromolyn sodium on the histamine release from RBL-2H3 cells line induced by DNP24-BSA as an antigen, and compare to it’s positive effect on active cutaneous anaphylaxis model induced by ovalbumin as an antigen. The results showed that cromolyn sodium did not inhibit the histamine release from RBL-2H3 cells line induced by DNP24-BSA significantly, but inhibited active cutaneous anaphylactic reaction induced by ovalbumin significantly.